The Role of Social Networks as a Tool for an Effective Recruitment Process in the Enterprises in Kosovo - Dragusha, Blerim; Prenaj, Vlora (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
This paper focuses on the determinants of the impact of social networks on the recruitment process in Kosovar enterprises, concluding that the main factor of that impact is the quality of information, cost benefits, and timeliness. Another factor of particular importance is the competitive advantages social networks provide with respect to efficiently attracting suitable candidates to recruit through their unified data processing speed. The managers interviewed in this study provided evidence that recruitment using social networks is faster than with traditional methods. Social networks enable firms to quickly and easily access applicants from all over the world easily at a low cost. Social networks provide in-depth discussions to understand the views and opinions of both parties in the recruitment process. The information provided by social networks on the personal and professional life of the potential job candidate makes social networks an important tool for recruitment